Modulation of APC Function and Anti-Tumor Immunity by Anti-Cancer Drugs - Martin, Kea; Schreiner, Jens; Zippelius, Alfred (Frontiers in Immunology, 2015)
Professional antigen-presenting cells, such as dendritic cells are central to the initiation and regulation of anti-cancer immunity. However, in the immunosuppressive environment within a tumor APCs may antagonize anti-tumor immunity by inducing regulatory T cells (Tregs) or anergy of effector T cells due to lack of efficient costimulation. Hence, in an optimal setting, anti-cancer drugs have the power to reduce tumor size and thereby, may induce the release of tumor antigens and, at the same time, modulate APC function towards efficient priming of antigen-specific effector T cells. Selected cytotoxic agents may revert APC dysfunction either by directly maturing DCs or through induction of immunogenic tumor cell death. Furthermore, specific cytotoxic agents may support adaptive immunity by selectively depleting regulatory subsets such as Tregs or myeloid-derived suppressor cells. Perspectively, this will allow developing effective combination strategies with novel immunotherapies to exert complementary pressure on tumors via direct toxicity as well as immune activation. We here review our current knowledge on the capacity of anti-cancer drugs to modulate APC functions to promote durable anti-cancer immune responses.